Effect of pinocembrin on thymocyte proliferation and death - Gulnoza Toshtemirova; Sarvinoz Rustamova; Nargiza Tsiferova; Galina Maksimcheva; Petr Merzlyak; Ranohon Kurbannazarova; Ravshan Sabirov (Journal of HerbMed Pharmacology, 2024)
Introduction: Cell volume regulation is critical for cellular proliferation and death. Pinocembrin effectively suppresses the volume regulation in thymocytes under hypoosmotic stress by blocking the volume-sensitive anion channel. This study aims to evaluate the effects of this flavonoid on thymocyte proliferation and death. Methods: Thymocytes were cultured in RPMI-1640 medium supplemented with 10% fetal bovine serum, and the cell number was determined by cloud-based automated cell counting (Corning). Necrotic and apoptotic cell death were evaluated by propidium iodide- and annexin V-staining, respectively. Results: Pinocembrin at 10–50 μM caused suppression of primary cultured thymocyte proliferation with a half-maximal effect of 28.4 ± 0.2 μM. The cell counts did not fall below the control level at the doses of 100–150 μM. The fraction of spontaneously necrotic cells was ~26% of the total population and increased to ~51% in the presence of dexamethasone. The fraction of spontaneously apoptotic cells increased by this glucocorticoid from 3.6% to 16.7%. Pinocembrin protected thymocytes from necrosis both in spontaneous and dexamethasone-induced death, reducing the fraction of necrotic cells by ~40–50% at 150 μM. Pinocembrin attenuated dexamethasone-induced apoptotic death, reducing the fraction of annexin-positive cells to the control (spontaneous) level. Conclusion: Our results suggest that pinocembrin arrests thymocyte proliferation without essential killing. Under conditions of massive death (e.g., during inflammation, when the level of glucocorticoids increases sharply both physiologically and as a result of pharmacotherapy), pinocembrin protects immuno-competent cells from necrotic and apoptotic death.